SAT0442 Functional disease status and healthcare costs in psoriatic arthritis: a similar relationship to that seen in rheumatoid arthritis. (15th June 2017) - Maguire, A; Handel, I; Tillett, W; Mughal, F; Morris, J; Hawkins, N; Cavill, C; Korendowych, E; McHugh, N
Abstract : Background: The Health Assessment Questionnaire-Disability Index (HAQ-DI), an important, validated measure of functional status in patients with psoriatic arthritis (PsA), has been used as an intermediate variable in modelling of costs and quality-adjusted life-years. The relationship between HAQ-DI and costs has been well documented for rheumatoid arthritis (RA), 1, 2 but less so for PsA. The HAQ-DI study data in PsA patients from the British Society for Rheumatology Biologics Registers was mapped to resource use data in the Health Improvement Network dataset. 3 A drawback of this approach relates to the HAQ-DI and resource use data being derived from separate patient cohorts. Objectives: Estimate the HAQ-DI and cost relationship in PsA within a single cohort of patients. Methods: Functional disease status, patient demographic, disease history and healthcare resource use data were extracted from a cohort of patients at the Royal National Hospital for Rheumatic Diseases. Resource data were available for primary and secondary care consultations, prescriptions, accident and emergency attendance, hospital admissions and tests, and collected for 6 months before and after HAQ-DI measurement. Medication costs were excluded from the modelling as it was not possible to specify which were PsA-related. Linear regression models were used to predict costs as a function of HAQ-DI and age at HAQ-DI measurement. As cost data were not normally distributed, standard errors (SEs), 95% confidence intervals (CIs) and P values were estimated by bootstrap resampling (10, 000 samples). Results: Data were available for 95 PsA patients (female: n=43). Mean HAQ-DI score was 0.81 (SE 0.08); mean age at HAQ-DI measurement was 58.6 (SE 1.04). Mean total annual healthcare costs, excluding medication costs, were £ 1, 588 (SE 172.3). Regression modelling indicated that a 1-point increase in HAQ-DI score was associated with an increase in total costs, excluding medications, of £ 547.49 (SE 222.7; 95% CI 191.7–1, 103.8; P =0.004) (Table). Subgroup analyses suggested trends for higher cost increases within the lower HAQ-DI cutoff subgroup (HAQ-DI 0–1) and for those with greatest disease duration (>10 years). Costs associated with secondary care consultations seemed to be the primary factor in the association between HAQ-DI and total costs. Conclusions: Models incorporating total healthcare costs were highly significant; this association appears to be driven mainly by secondary care consultation costs. Costs in this study were similar to previous studies in RA populations. A study limitation was that only direct medical costs were considered, which may underestimate the true burden of PsA on healthcare systems and the wider society. References: Lajas C, et al. Arthritis Rheum. 2003;49:64–70. Kobelt G, et al. Joint Bone Spine. 2008;75:408–15. Poole CD, et al. Rheumatology (Oxford). 2010;49:1949–56. Disclosure of Interest: A. Maguire Grant/research support from: Cogentia Healthcare Consulting Ltd, UK, I. Handel Consultant for: Visible Analytics Limited, W. Tillett: None declared, F. Mughal Employee of: Celgene Ltd, J. Morris Grant/research support from: Celgene Ltd, N. Hawkins Grant/research support from: Celgene Ltd, C. Cavill Grant/research support from: Celgene Ltd, E. Korendowych Grant/research support from: Abbvie, Celgene and Pfizer, Consultant for: Janssen, Abbvie, Novartis, Pfizer and Celgene, Speakers bureau: Janssen, Abbvie, Novartis, Pfizer and Celgene, N. McHugh Grant/research support from: Celgene Ltd